Two-photon direct laser writing of pNIPAM actuators in microchannels for dynamic microfluidics - Barwig, Chantal; Sonn, Annabelle; Spratte, Tobias; Mishra, Ankit; Blasco, Eva; Selhuber-Unkel, Christine; Pashapour, Sadaf (Advanced intelligent systems, 2024)
Microfluidic tools enable to investigate and manipulate various chemical and biological processes at small scales. As a result, it finds widespread applications in lab-on-chip devices, drug delivery systems, or miniaturized cell cultures. However, microfluidic devices are still limited in their flexibility and are often designed to fulfill a single functionality. Moreover, technologies to introduce dynamic functionalities with high precision and at high resolution after the development of a continuous phase microfluidic chip remain scarce. Herein, two-photon polymerization direct laser writing is introduced as a suitable approach to equip continuous phase microfluidic chips with structurally defined thermoresponsive poly(N-isopropyl-acrylamide) (pNIPAM) microactuators. Harnessing the lower critical phase transition temperature of pNIPAM, and upon controlling specific design parameters, the efficient catch and release of polystyrene beads of different sizes using a pNIPAM micropillar brush array is demonstrated. Moreover, a biocompatible pNIPAM microgripper array is designed to subsequently capture and release differently sized (single) cell populations. Overall, the method offers great flexibility and a high degree of freedom toward the fabrication of dynamic microfluidic devices with great adaptability to experimental conditions in real time.
Online veröffentlicht: 15. April 2024
Gesehen am 16.08.2024